Performance perceptions among supply chain members: A triadic assessment of the influence of supply chain relationship quality on supply chain performance - Odongo, Walter; Manoj, Dora; Molnár, Adrienn; Ongeng, Duncan; Gellynck, Xavier (British Food Journal., 2016)
A good supply chain relationship quality (RQ) is a crucial precursor for any stable exchange relationship which ensures relationship continuity. Although empirical research suggests that strengthening RQ improves supply chain performance (SCP), most studies have focused on dyadic business relationships. To fully understand the relational behaviour of a firm embedded in a supply chain, we need to look beyond the dyad into triads. The purpose of this paper is to investigate how SCP is influenced by RQ in a triadic agribusiness supply chain. Evidence is drawn from a quantitative survey of 150 agribusiness firms in the maize supply chain in Uganda. Data were collected in triadic context from 50 direct supply chains each composing of a supplier, focal firm and customer. Multi-group structural equations modelling (SEM) was used to assess the differences in perception on the influence of RQ on SCP amongst the supply chain members. Results provides empirical support for the positive influence of RQ on SCP. SEM reveals differences in perception between the upstream and downstream and amongst the supply chains members. While focal firms considered conflict, coercive power, commitment and trust to be important; suppliers considered trust, dependency and non-coercive power; and customers considered trust, dependency and coercive power to be important RQ factors affecting SCP.
Keywords: Supply chain performance, Supply chain relationship quality, Structural equations modelling, Agribusiness, Multi-group analysis